Determination of Concentration of Heavy Metals in Fruits, Vegetables, Groundwater, and Soil Samples of the Cement Industry and Nearby Communities and Assessment of Associated Health Risks - Ghazala Yaqub; Arooj Khan; Muhammad Zishan Ahmad; Umadia Irshad (Journal of Food Quality)
This study was conducted to estimate the heavy metal pollution in groundwater, soil, fruits, and vegetables within the cement industry and its vicinity. Seven different fruits and vegetables and seven heavy metals (Cd, Zn, Ni, Co, Cu, Cr, and Mn) were selected for analysis in soil, groundwater, fruit, and vegetable samples by atomic absorption spectrometry (AAS). Results of this study were compared with the National and International Standards of Pak NSWQD, WHO, and USEPA. The pH of soil and groundwater samples was within limits (WHO and Pak NSDWQ standards are 6.5–8.5). The concentration of Cr and Cu in groundwater samples was above the WHO and Pak NSDWQ standards (Cr = 0.05 ppm; Cu = 2 ppm). Vegetable samples were contaminated with metals except for Ni and Mn, whereas, in fruit samples, Mn and Cd were not present (WHO limit for Mn = 5 ppm). The mean concentration of Ni was high in fruits (WHO limit = 10 ppm), Zn was high in vegetables (WHO limit = 100 ppm), and Cu was high in soil and groundwater (WHO limit for soil = 36 ppm; for groundwater = 2 ppm). The results of daily intake of metals (DIM) for fruits, vegetables, and groundwater were compared with TDI by USEPA and PTDI of the WHO/FAO, and all were within the recommended limits. Calculated BAF for the selected environmental sample, that is, Indian Squash, lime fruit, and so on, was in order of Co > Cr > Cu and THQ; HRI was calculated to estimate the human health risk, and they were in a trend of Ni > Co > Cd > Cr and for HRI Co > Cr.